An evaluation of knowledge, attitudes, and behaviors of employees of a university hospital in an H1N1 influenza pandemic - Omer Evirgen; Nazan Savas; Vicdan Koksaldi Motor; Yusuf Onlen; Erhan Yengil (Journal of Infection in Developing Countries)
Introduction: In this study, we aimed to evaluate the knowledge, attitudes, and behaviors concerning the transmission routes of an H1N1 pandemic and the protective measures of health professionals at a university hospital in Turkey. Methodology: A stratified systematic sampling method was used to select the sample size of the study group. A total of 22 professors, 29 researchers, and 26 nurses were included in the study. Results: The mean scores of the individuals were 8.4±2.5 (over 20) for knowledge about H1N1 transmission, 27.6±4.0 (over 60) for knowledge about protection against H1N1, 25.8±4.2 (over 45) for correct or appropriate attitudes, and 33.6±8.9 (over 60) for correct behaviors. A negative correlation between total knowledge and behavior was found (p < 0.001, r = -0.543). Conclusions: In epidemics, standard protection measures should be known and applied. Regarding this topic, the web page of the Ministry of Health comes to the forefront as a reliable source of information in addition to scientific explanations.